The Memories of NK Cells: Innate-Adaptive Immune Intrinsic Crosstalk - Sara Gabrielli; Claudio Ortolani; Genny del Zotto; Francesca Luchetti; Barbara Canonico; Flavia Buccella; Marco Artico; Stefano Papa; Loris Zamai (Journal of Immunology Research)
Although NK cells are considered part of the innate immune system, a series of evidences has demonstrated that they possess characteristics typical of the adaptive immune system. These NK adaptive features, in particular their memory-like functions, are discussed from an ontogenetic and evolutionary point of view.